2009
DOI: 10.1002/pd.2386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of regional left ventricular longitudinal function in 151 normal fetuses using velocity vector imaging

Abstract: VVI is a novel noninvasive tool for quantitative assessment of regional systolic and diastolic function of the fetal heart. Fetal myocardial velocity, strain, and strain rate measurements can be measured easily and reproducibly. This technique is useful for evaluating cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 14 publications
10
63
0
1
Order By: Relevance
“…233,[308][309][310][311][312][313][314][315][316][317][318][319] Several of these studies have applied 2D speckle tracking echocardiography to the normal midgestation to late-gestation fetus for the assessment of longitudinal mechanics, although only 1 study to date has also addressed circumferential strain. 318 In general, feasibility is reasonable, although some studies have reported up to 20% to 30% interobserver variability.…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 99%
“…233,[308][309][310][311][312][313][314][315][316][317][318][319] Several of these studies have applied 2D speckle tracking echocardiography to the normal midgestation to late-gestation fetus for the assessment of longitudinal mechanics, although only 1 study to date has also addressed circumferential strain. 318 In general, feasibility is reasonable, although some studies have reported up to 20% to 30% interobserver variability.…”
Section: Strain and Strain Rate Imagingmentioning
confidence: 99%
“…Speckle tracking is a non-Doppler technique based on offline 2D image analysis that measures tracking of myocardial speckles frame by frame to allow assessment of myocardial deformation. Normal values have been described in the fetus [1,2,3,4,5,6,7,8,9], including a contemporaneous study by our group in the same population as this report [6]. Potential advantages include no extra scanning time, relative angle independence, and the ability to use stored images.…”
Section: Introductionmentioning
confidence: 92%
“…As with all fetal myocardial-derived indices, factors such as maternal-fetal movements, suboptimal imaging, and a low frame rate limit its clinical application [125]. To date, 2D speckle tracking has been investigated in terms of its feasibility and application to fetal echocardiography [126,127,128,129,130,131,132,133,134]; however, further studies evaluating its use in pathological conditions are warranted.…”
Section: Future Research Directionsmentioning
confidence: 99%